Benzyl C–O and C–N Bond Construction via C–C Bond Dissociation of Oxime Ester under Visible Light Irradiation. Issue 10 (5th September 2019) - Fan, Xiuwei; Lei, Tao; Liu, Zan; Yang, Xiu‐Long; Cheng, Yuan‐Yuan; Liang, Ge; Chen, Bin; Tung, Chen‐Ho; Wu, Li‐Zhu
Abstract : A photoredox benzyl activation was developed via formidable C(sp 3 )–C(sp 3 ) bond dissociation of 1‐aryl acetone oxime esters, which were easily prepared from benzyl ketones. Further coupling with O‐ and N‐ nucleophiles successfully forged important benzyl ether and amines derivatives in one pot. In this process, different substitutions on oxime esters were found compatible and various primary and secondary alcohols and amines, as well as amides showed good performance as nucleophiles. Mechanistic studies by control experiments, electrochemical measurements and in‐situ NMR spectra proposed a N–O bond interruption/C–C bond fragmentation/oxidation sequence to provide the key cation intermediate for the next electrophilic SN process. The features of mild condition, short reaction time and broad substrate scope made this new strategy much promising in the transformation of benzyl compounds, which might be valuable in last‐stage functionalizations. Abstract : A photoredox benzyl activation was developed via formidable C(sp 3 )–C(sp 3 ) bond dissociation of 1‐aryl acetone oxime esters, easily prepared from benzyl ketones. The generated benzyl cation coupling with diverse O ‐ and N ‐ nucleophiles successfully forged important benzyl ether and amines derivatives that are valuable in last‐stage functionalizations.